The role of epistemic curiosity in the self-directed learning of graduates who have transitioned to the workplace and completed a structured graduate programme - Stewart, Celeste (Graduate School of Business, 2026)
This qualitative study explores and focuses on the role of curiosity in cultivating self-directed learning for graduates who have transitioned into the workplace. Young people make a significant transition when moving from the world of studies to the world of work. Their success as full-time employees depends on several factors, including their ability to engage their curiosity, stay motivated, and drive their own learning. This approach to learning requires the learner to be in the driving seat and fully engaged, which contrasts with the more passive learning experienced at school and university, where the learner is a receiver rather than a driver of knowledge and learning. The study assumes that the more engaged the learner, the more value they will derive from the learning experience. As a motivational state, this inner drive begins to build habits for adult learning that set them up well for the future. The study sample consisted of 20 participants—10 graduates and 10 mentors—as it was important to gather perspectives from both graduates and the mentors who support them. Data was collected through semi-structured interviews, and thematic analysis was used to identify the key themes that emerged. The interviews explored how participants viewed curiosity and self-directed learning, whether and how they engaged with their own learning while in the graduate programme, the role of curiosity in their learning, and the benefits of engaging with their curiosity and learning. The study's key themes are: inner drive, exploration, ownership, resilience, and community. Findings suggest that curiosity catalyses deeper engagement with learning material, fostering resilience and intrinsic motivation. However, external factors, such as rigid curricula and fear of failure, often stifle this natural inclination. Furthermore, the study suggests that epistemic curiosity drives intrinsic motivation, deeper engagement and ownership of learning, a drive for comprehension and sense-making, and a sense of resilience within their curiosity or exploratory behaviour. Participants also highlighted the challenges of a lack of curiosity, such as feeling unsafe to explore and an intolerant learning environment, which stifled growth. The mentors' role in advocating for the graduates and creating a supportive learning environment was highlighted. Additionally, mentors were found to play a key role in creating the psychological safety required for learning by being vulnerable and sharing their own experiences. The study concludes by highlighting the importance of creating educational environments that nurture curiosity. It offers insights for educators seeking to design curricula and teaching strategies that promote lifelong learning. These findings contribute to the broader discourse on studentcentred learning and emphasise curiosity as a critical yet underutilised component of educational practice within the South African context.